Seasonal Variations of Mesospheric Gravity Waves Observed with an Airglow All-sky Camera at Mt. Bohyun, Korea (36° N) - Yong Ha Kim; Changsup Lee; Jong-Kyun Chung; Jong-Kyun Chung; Hye-Yeong Chun (Journal of Astronomy and Space Sciences, 2010)
We have carried out all-sky imaging of OH Meinel, O2 atmospheric and OI 557.7 nm airglow layers in the period from July of 2001 through September of 2005 at Mt. Bohyun, Korea (36.2° N, 128.9° E, Alt = 1,124 m). We analyzed the images observed during a total of 153 clear moonless nights and found 97 events of band-type waves. The characteristics of the observed waves (wavelengths, periods, and phase speeds) are consistent with internal gravity waves. The wave occurrence shows an approximately semi-annual variation, with maxima near solstices and minima near equinoxes, which is consistent with other studies of airglow wave observations, but not with those of mesospheric radar/lidar observations. The observed waves tended to propagate westward during fall and winter, and eastward during spring and summer. Our ray tracing study of the observed waves shows that majority of the observed waves seemed to originate from mesospheric altitudes. The preferential directions and the apparent source altitudes can be explained if the observed waves are secondary waves generated from primary waves that have been selected by the filtering process and break up at the mesospheric altitudes.